Infectivity and stress tolerance traits affect community assembly of plant pathogenic fungi - Choi, Soyoung; Yang, Jung Wook; Kim, Jung-Eun; Jeon, Hosung; Shin, Soobin; Wui, Dayoun; Kim, Lee Seul; Kim, Byung Joo; Son, Hokyoung; Min, Kyunghun (Frontiers in Microbiology, 2023)
Understanding how ecological communities assemble is an urgent research priority. In this study, we used a community ecology approach to examine how ecological and evolutionary processes shape biodiversity patterns of plant pathogenic fungi, Fusarium graminearum and F. asiaticum. Highthroughput screening revealed that the isolates had a wide range of phenotypic variation in stress tolerance traits. Net Relatedness Index (NRI) and Nearest Taxon Index (NTI) values were computed based on stress-tolerant distance matrices. Certain local regions exhibited positive values of NRI and NTI, indicating phenotypic clustering within the fungal communities. Competition assays of the pooled strains were conducted to investigate the cause of clustering. During stress conditions and wheat colonization, only a few strains dominated the fungal communities, resulting in reduced diversity. Overall, our findings support the modern coexistence theory that abiotic stress and competition lead to phenotypic similarities among coexisting organisms by excluding large, lowcompetitive clades. We suggest that agricultural environments and competition for host infection lead to locally clustered communities of plant pathogenic fungi in the field.